Star Fruit Orchard Waste as Source of Organic Materials On Sustainable Agricultural System - Sumiasih, Inanpi Hidayati; Puspitawati, Mutiara Dewi; Fauzi, Ahmad Rifqi (Journal of Tropical Horticulture, 2020)
Star fruit harvesting activity in Attaqie Farm orchard produces no less than 20% of organic waste in each period. The organic waste can be utilized as an organic fertilizer source. The potential of star fruit waste as a source for liquid organic fertilizer (LOF) is an interesting subject to study. The objective of this study was to obtain information about the potential of star fruit waste as LOF and how it affects green mustard production. The study used the factorial design with two factors, namely inorganic fertilizer dosage (0%, 50%, and 100% of recommended dosage) and LOF concentration (0, 3, 6, and 9 ml/L) and arranged using Completely Randomized Block Design. There were twelve combinations of treatments with three replications. The production of liquid organic fertilizer (LOF) with star fruit waste as the main ingredient used an anaerobic fermentation method with help from EM4 bio-activator for 30 days. Green mustard shoot weight increased with higher LOF concentration. The application of 9 ml/L LOF produced 20% higher green mustard shoot weight compared to without application and the application of 3 ml/L LOF. The result showed that LOF from star fruit waste has the potential to be developed through formulation development.